Evaluation Study of The Existing Condition Of Drainage Channels In Bangkinang Kota District (Case Study: Petai River III) - Hudin, M. Hisam; Adeswastoto, Hanantatur; Febryanto (Journal of Engineering Science and Technology Management (JES-TM), 2025)
The development of the city followed by an increase in the population in Bangkinang City has resulted in the conversion of land functions into residential areas or offices, resulting in disruption of soil absorption capacity and increased surface runoff and resulting in flooding. This final project aims to analyze the ability of existing drainage channels to accommodate and flow flood discharge, analysis of maximum planned rainfall, analysis of planned flood discharge with a return period. The research method used is the method of field data and data analysis. The data used are primary data and secondary data. The discharge value of the existing channel with the planned discharge value is analyzed based on hydrological analysis and hydraulic analysis. This study uses the Log Person Type III distribution because it gives the best results compared to other distributions. Results The calculated rainfall intensity for the 10-yearreturn period is 109.0159 mm/hour. The design discharge is calculated based on the Rational method, it is known that the 10 year return period is Q = 26.3266 m3/s. From the dimensional analysis it turned out that the drainage channel for Jalan Mayor Ali Rasyid was not able to accommodate the discharge of the planned channel, and a width of 1.2 m was added along the flood area, and the channel could accommodate the runoff that occurred in the Petai III river.